Intersections of Inflammatory Bowel Disease (IBD) and Non‑Alcoholic Fatty Liver Disease (NAFLD): A PRISMA‑ScR Guided Scoping Review - Lubis, Mhd Asrul (Asian Multidisciplinary Research Journal of Economy and Learning, 2025)
Inflammatory bowel disease (IBD) and non-alcoholic fatty liver disease (NAFLD) are two chronic conditions with increasing global prevalence, both associated with systemic inflammation, metabolic dysfunction, and alterations of the gut–liver axis. Recent evidence highlights a bidirectional relationship, where IBD patients show higher prevalence of NAFLD, while NAFLD is increasingly recognized as a comorbidity influencing IBD outcomes. Despite these intersections, the extent of overlap, shared mechanisms, and therapeutic implications have not been comprehensively mapped. This scoping review aimed to summarize the available literature addressing the interplay between IBD and NAFLD, with a focus on epidemiology, mechanisms, and therapeutic strategies. A systematic search was conducted across PubMed, Embase, Scopus, and Web of Science from 2015 to June 2025. Eligible studies included randomized controlled trials, observational cohorts, cross-sectional analyses, and translational research that evaluated the coexistence of IBD and NAFLD, shared pathophysiological mechanisms, or interventional approaches. Study selection followed PRISMA-ScR guidelines. Data were charted into evidence tables and synthesized narratively and with evidence mapping. Thirty studies were included: 15 focusing primarily on IBD with NAFLD relevance, and 15 addressing NAFLD with implications for IBD. Key findings demonstrated consistent associations between IBD and increased NAFLD prevalence, with obesity and metabolic syndrome as major risk enhancers. Shared mechanisms included microbial dysbiosis, bile acid metabolism, and proinflammatory cytokine pathways. Interventions such as probiotics, synbiotics, fecal microbiota transplantation, and metabolic agents (GLP-1 receptor agonists, SGLT2 inhibitors) showed cross-disease benefits, though evidence remains heterogeneous and largely preclinical or early-phase clinical. IBD and NAFLD represent overlapping inflammatory-metabolic conditions with significant clinical impact. Current evidence supports integrated management and early screening, yet robust interventional trials targeting both conditions are lacking. Future research should prioritize longitudinal and therapeutic studies to clarify causal pathways and optimize care.